Improved Grey Wolf Optimization for Economic Load Dispatch Problem Considering Valve Point Loading Effect and Prohibited Operating Zones - Mehmood, K.; Ahmad, A. (The Nucleus, 2018)
Economic load dispatch (ELD) is an important power system operational planning problem. In the past, calculus based techniques have been used for solving convex ELD problem. The practical ELD problem is non convex due to valve point effect. This paper presents a new improved grey wolf optimization (IGWO) for solving ELD problem considering constraints such as valve point effect, transmission losses and prohibited operating zones. Grey wolf optimization (GWO) is a swarm intelligence (SI) technique which suffers from stagnation. To overcome this problem differential mutation and crossover operations are combined with GWO to form IGWO. The proposed IGWO is successfully implemented on 6, 13, 15 and 40 thermal units test systems. For validation, results are compared with recent techniques. This comparison proves the superiority of IGWO.